Substance use in young adults with ADHD: Comorbidity and symptoms of inattention and hyperactivity/impulsivity - Ana Miranda (International Journal of Clinical and Health Psychology, 2016)
Young adults with attention deficit hyperactivity disorder (ADHD) are at high risk of substance use (SU). The aims of the current study were: 1) to examine the use of alcohol, tobacco, marijuana and other illegal drugs by adults with and without ADHD; 2) to compare the oppositional, conduct, anxiety, depression, sleep and antisocial personality symptoms of ADHD adults with SU and ADHD adults without SU; 3) to examine the ability of ADHD symptoms and conduct problems to predict SU. A total of 93 young adults, 43 without ADHD and 50 with a childhood diagnosis of ADHD, who were part of the Spanish sample of the Multicenter ADHD Genetics (IMAGE) study, collaborated in a follow-up evaluation 10.1 years later. ADHD participants were divided into two groups based on the presence or absence of SU. Statistically significant differences were found between young adults with and without ADHD in their use of tobacco, marijuana and alcohol. A statistically significant association was also shown between externalization problems and a greater risk of SU. Conduct problems, to a greater degree than ADHD symptoms, affect SU in ADHD adults.